Plain radiographs can be used for routine assessment of ACL reconstruction tunnel position with three-dimensional imaging reserved for research and revision surgery - Kosy, Jonathan David; Mandalia, Vipul I. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2018)
Purpose The position of the osseous tunnels and graft during anterior cruciate ligament (ACL) reconstruction has been the subject of multiple studies aiming for either anatomical placement or an alternative. The assessment of these positions, using post-operative imaging, is therefore of interest to the surgeon in both the evaluation of surgical performance and surveillance of potential complications. The purpose of this review is to identify the optimal use of imaging in both the surveillance of clinical practice and in planning revision surgery. Methods A comprehensive systematic review was performed using Medline and Pubmed searches to identify radiological methods used to assess ACL reconstruction tunnel position. Commonly used methods were identified with correlation to either native anatomy or clinical results. Results The findings suggest that plain radiographs can be used to assess tunnel position and identify grafts that are positioned non-anatomically and may be at increased risk of complications. Computer tomography (CT) offers additional information about the tunnel aperture shape and size that is of importance for revision surgery and research projects whilst magnetic resonance imaging (MRI) provides further assessment of both graft integrity and associated soft tissue damage. Conclusion In the surveillance of routine clinical practice, plain radiographs are sufficient to define tunnel position. The additional information provided by three-dimensional imaging is only required in revision surgery or research studies. Level of evidence IV.